Law of administrative organization of the EU a comparative approach - Ruffert, Matthias 1966- (Edward Elgar Publishing, 2020)
With the transfer of ever more tasks and competences to the European level the EU's administration has become increasingly complex, with 'agencification' as the most visible sign of this differentiation. This book offers a much-needed analytical overview of the field, with the aim of improving our understanding of administration at the European level, and indeed of improving the administration itself
Keywords: Europäische Union; Verwaltungsrecht; Administrative law / European Union countries; Administrative agencies / European Union countries; Electronic books